Educational backgrounds in inventor teams : the role of complementarities between academic and vocational education in team performance - Bruestle, Bastian Silvester [Verfasser]; Lehnert, Patrick [Verfasser]; Buunk, Erik [Verfasser]; Backes-Gellner, Uschi [Verfasser]; Harhoff, Dietmar [Verfasser] (My University, 2025)
“This paper analyzes whether inventor teams composed of members with diverse educational backgrounds, both academic and vocational, exhibit higher performance than teams with the same educational backgrounds. To exploit the different educational backgrounds among patent inventors in Switzerland, we construct a unique dataset of 35,486 inventors. This dataset links individual patenting activities from European Patent Office data from 1980-2021, with detailed biographical information obtained from LinkedIn. Using a supermodularity framework to assess complementarity, we find that inventor teams composed of members with academic and vocational backgrounds (as opposed to members with the same background) achieve higher team performance, measured by the quality of their jointly filed patents. This complementarity is even stronger in teams with at least one team member from a University of Applied Sciences. Further analysis reveals heterogeneous effects across technological fields. Overall, our findings show the importance of strategically combining different educational backgrounds in inventor teams, thereby highlighting the value of maintaining a balanced educational landscape.“ (authors’ abstract; BIBB-Doku)
Keywords: G 1.2.3.1 Potenziale; 370; Erfindung; Patente; Team; Teamfähigkeit; Teamarbeit; Heterogenität; Bildungsabschluss; Qualifikationsniveau; Akademiker; Fachkräfte; Schweiz